2014
DOI: 10.3389/fenvs.2014.00037
|View full text |Cite
|
Sign up to set email alerts
|

Multi-decadal classification of synoptic weather types, observed trends and links to rainfall characteristics over Saudi Arabia

Abstract: An automated version of the Lamb weather type classification scheme was employed to characterize daily circulation conditions in Saudi Arabia from 1960 to 2005. Daily gridded fields of sea level pressure (SLP) from both the NCEP/NCAR and the European Center for Medium-Range Weather Forecast (ECMWF) reanalysis data (ERA40) were used as input data for this classification. The output catalog included 10 basic types, which describe the direction and vorticity of airflow in the region (i.e., cyclonic, anti-cyclonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…The previous studies (e.g., Almazroui et al 2013, Barfus andBernhofer 2014) examined the performance of CMIP3 models over the Arabian Peninsula in the present day climate. Some other studies also provided insight into recent climate change and extremes over the Arabian Peninsula (e.g., Almazroui et al 2012a, b;Deng et al 2015;Donat et al 2014;El Kenawy et al 2014;AlSarmi and Washington 2011, Kwarteng et al 2009Evans 2009). However, a comprehensive analysis of the uncertainties associated with future projections over the Arabian Peninsula for different categories of CMIP3 models including well performing models compared to the observations is missing in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies (e.g., Almazroui et al 2013, Barfus andBernhofer 2014) examined the performance of CMIP3 models over the Arabian Peninsula in the present day climate. Some other studies also provided insight into recent climate change and extremes over the Arabian Peninsula (e.g., Almazroui et al 2012a, b;Deng et al 2015;Donat et al 2014;El Kenawy et al 2014;AlSarmi and Washington 2011, Kwarteng et al 2009Evans 2009). However, a comprehensive analysis of the uncertainties associated with future projections over the Arabian Peninsula for different categories of CMIP3 models including well performing models compared to the observations is missing in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity test of Unclassified days on grid sizes and resolutions was performed in Demuzere et al (2009b), concluding that the number of these days would decrease with grid resolution. Other authors did not consider the Unclassified type due to the few cases in the particular study area and they decided to regroup Unclassified days among the retained classes (Trigo and DaCamara 2000;Cortesi et al 2013;El Kenawy et al 2014). Previous studies found a significant increase of portion of Unclassified days in summer and autumn when applying JC classification.…”
Section: Classification Of Wt: a Gridded Jc-implementationmentioning
confidence: 99%
“…An extensive number of studies that use the JC procedure can been found in the literature and they have mainly focused on Europe: Trigo and DaCamara (2000), Linderson (2001), Goodess and Jones (2002), Spellman (2000), Chen (2000), Grimalt et al (2012), Lorenzo et al (2008), Post et al (2002), Buishand and Brandsma (1997), Cortesi et al (2013), among others. Besides these areas, this scheme has been applied in other regions where it has been rarely used so far, such as USA (Wilby et al 1995), China (Liwei et al 2006), Taiwan (Lai 2010), Chile (Espinoza et al 2014), the Arabian Peninsula (El Kenawy et al 2014), or Russia (Spellman 2015). Given the numerous existing studies in which the JC classification has been applied, we aim to contribute with a geographically extended implementation of the original scheme.…”
Section: Introductionmentioning
confidence: 99%
“…in Saudi Arabia (Kenawy et al, 2014). Recently, 20 this method was used by Reyers et al (2013) to determine present day and future high-resolution rainfall distributions in the Aksu river basin (on the southern slopes of the Tien-Shan Mountains, CA).…”
Section: Circulation Weather Types (Cwt) 10mentioning
confidence: 99%